Biomass-derived active carbon (AC) modified AgO photocatalyst for efficient photocatalytic degradation of methylene blue dye under visible light - Mehifer khadidja nassra; BRAHIMI Djamila (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2024)
In this study, activated carbon (AC) from walnut shell, was synthesised in a simple two-step procedure (Carbonation and Activation) and used to produce a catalyst AgO/AC (silver oxide supported on activated carbon) for the degradation of methylene blue (MB) dye under visible light. The research explores the influence of various parameters on photocatalytic activity, such as light source, initial concertation of MB dye, time, weight ratio of AgO/AC, and pH. The findings revealed that increasing catalyst dose and irradiation time enhanced MB degradation, while higher initial dye concentration led to a decrease in the photodegradation rate. Light significantly boosted the degradation rate compared to dark conditions. Interestingly, MB dye photodegradation rate increased with increasing pH, with the best removal efficiency observed at pH 12. Using Ago-AC as a photocatalyst for organic pollutants removal from wastewater could have promising results due to its high photodegradation rate.
Petrochemical engineering